Obesity risk is associated with brain glucose uptake and insulin resistance. Issue 6 (30th November 2022) - Pekkarinen, Laura; Kantonen, Tatu; Rebelos, Eleni; Latva-Rasku, Aino; Dadson, Prince; Karjalainen, Tomi; Bucci, Marco; Kalliokoski, Kari; Laitinen, Kirsi; Houttu, Noora; Kirjavainen, Anna K; Rajander, Johan; et al.
Abstract: Objective: To investigate whether alterations in brain glucose uptake (BGU), insulin action in the brain–liver axis and whole-body insulin sensitivity occur in young adults in pre-obese state. Methods: Healthy males with either high risk (HR; n = 19) or low risk (LR; n = 22) for developing obesity were studied with [ 18 F]fluoro-d -glucose ([ 18 F]FDG)–positron emission tomography during hyperinsulinemic–euglycemic clamp. Obesity risk was assessed according to BMI, physical activity and parental overweight/obesity and type 2 diabetes. Brain, skeletal muscle, brown adipose tissue (BAT), visceral adipose tissue (VAT) and abdominal and femoral s.c. adipose tissue (SAT) glucose uptake (GU) rates were measured. Endogenous glucose production (EGP) was calculated by subtracting the exogenous glucose infusion rate from the rate of disappearance of [ 18 F]FDG. BGU was analyzed using statistical parametric mapping, and peripheral tissue activity was determined using Carimas Software imaging processing platform. Results: BGU was higher in the HR vs LR group and correlated inversely with whole-body insulin sensitivity (M value) in the HR group but not in the LR group. Insulin-suppressed EGP did not differ between the groups but correlated positively with BGU in the whole population, and the correlation was driven by the HR group. Skeletal muscle, BAT, VAT, abdominal and femoral SAT GU were lower in the HR group as compared to the LR group. Muscle GU correlated negatively with BGU in the HR group but not in the LR group. Conclusion: Increased BGU, alterations in insulin action in the brain–liver axis and decreased whole-body insulin sensitivity occur early in pre-obese state.